Assessment of women involvement in locust beans processing in Ejigbo Local Government Area - Alao, Oluwagbenga Titus; Amossou, Tobi Esnade; Abioye, Gabriel Ifeoluwa (Indonesian Journal of Agricultural Research, 2025)
A two-stage selection technique was employed to randomly pick the benefits, profitability analysis, and restrictions associated with women's participation in locus bean production within designated villages in Ejigbo Local Government Area, Osun State, Nigeria. A structured interview protocol was employed to collect primary data from 120 respondents. Collected data were analyzed using descriptive and inferential statistics executed with Statistical Package for the Social Sciences. The respondent’s average family size was 6 individuals with 73.33% of the respondents between the ages of 14 and 60 being married women. Also, 23.33% of the respondents possessed secondary education, with 2% attaining tertiary education. Likewise, 72% of the respondents identify as Christian, with 62.50% obtaining the requisite abilities for this enterprise from their parents. Furthermore, 67.50% utilized domestic labor for executing procedures involved in locust bean production. The profitability analysis revealed that each N1 invested in the enterprise generated a profit of N0.35, indicating the profitability of the firm as an alternative for additional income. Furthermore, processing experience in terms of year and age exhibited a positive and significant correlation; household size demonstrates a positive yet non-significant correlation, years of education indicate a negative and significant correlation. Conclusively, women's involvement in locust bean processing is a lucrative venture, but face challenges like inadequate financing, high costs of raw materials, firewood, and transportation. Consequently, governments and non-governmental organizations should promote the engagement of young graduates in local bean processing by supplying time-efficient machinery and contemporary processing apparatus, in addition to connecting them with established marketplaces.